2016
DOI: 10.1016/j.compfluid.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

A well-balanced positivity-preserving central-upwind scheme for shallow water equations on unstructured quadrilateral grids

Abstract: We introduce a new second-order central-upwind scheme for shallow water equations on the unstructured quadrilateral grids. We propose a new technique for bottom topography approximation over quadrilateral cells as well as an efficient water surface correction procedure which guarantee the positivity of the computed fluid depth. We also design a new quadrature for the discretization of the source term, using which the new scheme exactly preserves "lake at rest" steady states. We demonstrate these features of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…For instance, at this year's SIAM CSE conference 2 , there was a dedicated session on Positivity Preserving and Invariant Domain Preserving Methods, where many of the talks addressed these issues for high-order methods. Some of the more recent publications include [151,152,61,19,121]. Hence, simpler methods may be more convenient when we are dealing with very complex flows, such as multiphase flow models or flows with strong source terms.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, at this year's SIAM CSE conference 2 , there was a dedicated session on Positivity Preserving and Invariant Domain Preserving Methods, where many of the talks addressed these issues for high-order methods. Some of the more recent publications include [151,152,61,19,121]. Hence, simpler methods may be more convenient when we are dealing with very complex flows, such as multiphase flow models or flows with strong source terms.…”
Section: Motivationmentioning
confidence: 99%
“…Notable results include the paper by Einfeldt et al [34], where it is shown that the Godunov and HLLE schemes are positivity preserving, while the Roe scheme is not, the paper by Batten et al [6] where they showed that the HLLC [139] scheme is positivity preserving with an appropriate choice of wave velocity estimates, the work by Perthame and Shu [116] where they established a general framework to achieve high-order positivity preserving methods for the Euler equations in one and two dimensions, and the book by Bouchut [11] where the conditions on the wave velocities estimates are determined so that the HLLC scheme can also handle vacuum. Areas of interest include the Euler equations (Calgaro et al [14], Hu et al [61], Li et al [87], Zhang and Shu [150,151,152]), shallow water equations [121,71,147,3], magnetohydrodynamics [4,67,40], multiphase flows (Chen and Shu [18]), unstructured meshes (Berthon [8]) and flux-vector splitting methods (Gressier et al [46]), to name just a few. These papers consider standard methods and mostly tackle issues with positivity preserving that arise in high-order methods.…”
Section: Definition 3 (Einfeldt Et Al [34])mentioning
confidence: 99%
“…These models are based on the twodimensional shallow water equations. Over the past few years, several 2D models have been developed using various numerical methods such as finite difference (FD) [2], finite element (FE) [3], and finite volume methods (FV) [4]. DELFT3D and MIKE21 are among the widely used 2D numerical models can be used for river hydrodynamics simulations.…”
Section: Introductionmentioning
confidence: 99%
“…For this second test case, we consider a hypothetical twodimensional dam break problem with nonsymmetric breach that is a typical validation made in many presented papers, for example, [30][31][32][33]. An illustration of this problem is shown in Figure 3 …”
Section: Two-dimensional Partial Dam Break Simulationmentioning
confidence: 99%